(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the pedagogical significance of simulation-based learning technologies in teaching neonatal care. Modern medical education requires not only theoretical knowledge but also well-developed practical skills, especially in high-risk areas such as neonatology. The study analyzes the effectiveness of simulation-based training in improving clinical competence, decision-making ability, and professional readiness of medical students. Special attention is given to the development of practical skills in managing critical neonatal conditions such as Neonatal asphyxia and Respiratory distress syndrome. The results indicate that simulation-based education significantly enhances students’ clinical performance, promotes active learning, and reduces the likelihood of medical errors. It also improves communication, teamwork, and stress management skills, which are essential in neonatal intensive care. The study concludes that integrating simulation technologies into neonatal education is an effective approach to improving the quality of medical training and ensuring patient safety.